HBR guide to remote work. (Harvard business review guides., 2021)
The HBR Guide to Remote Work provides practical tips and advice to help you stay productive, avoid distractions, and collaborate with your team, despite the distance that separates you. You'll learn to: Create a regular work-from-home routine Identify the right technology for your needs Run better virtual meetings Avoid burnout and video-call fatigue Manage remote employees Conduct difficult conversations when you can't meet in person Arm yourself with the advice you need to succeed on the job, with the most trusted brand in business. Packed with how-to essentials from leading experts, the HBR Guides provide smart answers to your most pressing work challenges.